Artivism Unveiled: Tracing the Historical and Aesthetic Roots of Artistic Activism in South Asia - Nicolas Nercam (South Asia Multidisciplinary Academic Journal)
The aim of this contribution is to provide a comprehensive exploration of the historical and artistic dimensions of contemporary artistic activism in South Asia. Focusing on modern and contemporary visual art history, it identifies key milestones in the relationship between art and politics in the region—a rich and extensive history stretching from the early 20th century during the anti-colonial struggle to the geopolitical shifts of the 1990s. Over this period, the dynamic interplay between art and politics gave rise to groundbreaking artistic forms, shaping the perspectives of contemporary activism in South Asia, whether through rejection or adoption. Employing a chronological approach to this subject allows for an understanding of the major trends that characterize the art field in a rapidly changing context. Simultaneously, the examination of specific regional examples helps identify expressions of the evolving connection between aesthetics and politics, shedding light on the distinctive and fluid role of artists engaged in political expressions.